2011
DOI: 10.1016/j.hrthm.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous electrocardiogram alterations predict ventricular fibrillation in Brugada syndrome

Abstract: ECG alterations, especially conversion between types 0 and 1, are associated with significant AP heterogeneity that can initiate VF in BS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…Type I, II, and III Brugada patterns were defined according to standard criteria and as endorsed by the Consensus Document, 1 including recent important updates on the ECG diagnosis of Brugada syndrome 14 with the only exception that an ECG with a right bundle branch block pattern and classic coved-type ST-segment elevation was considered type I even in the absence of negative T waves in leads V 1 –V 3 . This is because when a coved ST segment-elevation is obvious , (1) the presence of inverted T waves is no longer considered a requisite for defining Brugada syndrome by most experts; (2) ECGs in a patient with typical coved type I pattern may or may not have a negative T wave on different days 15 ; and (3) the prognosis of coved-type ST-segment elevation without T-wave inversion is similar to that of the “classic” type I pattern. 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I, II, and III Brugada patterns were defined according to standard criteria and as endorsed by the Consensus Document, 1 including recent important updates on the ECG diagnosis of Brugada syndrome 14 with the only exception that an ECG with a right bundle branch block pattern and classic coved-type ST-segment elevation was considered type I even in the absence of negative T waves in leads V 1 –V 3 . This is because when a coved ST segment-elevation is obvious , (1) the presence of inverted T waves is no longer considered a requisite for defining Brugada syndrome by most experts; (2) ECGs in a patient with typical coved type I pattern may or may not have a negative T wave on different days 15 ; and (3) the prognosis of coved-type ST-segment elevation without T-wave inversion is similar to that of the “classic” type I pattern. 15 …”
Section: Methodsmentioning
confidence: 99%
“…This is because when a coved ST segment-elevation is obvious , (1) the presence of inverted T waves is no longer considered a requisite for defining Brugada syndrome by most experts; (2) ECGs in a patient with typical coved type I pattern may or may not have a negative T wave on different days 15 ; and (3) the prognosis of coved-type ST-segment elevation without T-wave inversion is similar to that of the “classic” type I pattern. 15 …”
Section: Methodsmentioning
confidence: 99%
“…113 A prospective study using signal-averaged ECG suggested that positive late potential may have predictive value of malignant arrhythmic events in BrS. 107 Of note, these studies were performed in a small number of patients and deserved further evaluation with a larger cohort.…”
Section: Insight Into Brugada Syndrome An Updatementioning
confidence: 99%
“…Fourth, the prevalence of Brugada syndrome in the present study might have been underestimated because Brugada-like ECG pattern changes over time. 30 Fifth, although 10 patients had early repolarization ECG pattern, of which the presence is indicated as a high risk for fatal VAs, 18 we were unable to elucidate its impact on the results of dual induction tests. Sixth, the small sample size of our subjects did not allow us to compare the long-term prognosis among groups classified by the dual induction test, with an appropriate correction for baseline differences.…”
Section: Study Limitationsmentioning
confidence: 89%